Glycosylation of voltage-gated calcium channels in health and disease - Lazniewska, Joanna; Weiss, Norbert (Biochimica et biophysica acta. Biomembranes, 2017)
Voltage-gated calcium channels (VGCCs) are transmembrane proteins that translate electrical activities into intracellular calcium elevations and downstream signaling pathways. They serve essential physiological functions including communication between nerve cells, muscle contraction, cardiac activity, and release of hormones and neurotransmitters. Asparagine-linked glycosylation has emerged as an essential post-translational modification to control the number of channels embedded in the plasma membrane but also their functional gating properties. This review provides a comprehensive overview about the current state of knowledge on the role of glycosylation in the expression and functioning of VGCCs, and discusses how variations in the glycosylation of the channel proteins can contribute to pathological conditions.
Keywords: Calcium Channels; Neuropathic pain; Diabetes Mellitus, Experimental; Humans; Ancillary subunit; podjednotky proteinů; experimentální diabetes mellitus; Calcium channels; Stability; lidé; zvířata; Diabetes; Trafficking; glykosylace; Plasma membrane; Protein Subunits; vápníkové kanály; Animals; N-glycosylation; Glycosylation; Voltage-gated calcium channels